Effects of COVID-19 virus-like particles on the behavioral and cognitive performance of human apolipoprotein E targeted replacement mice - O’Niel, Abigail; Pederson, Alexandra; Saltontall, Elizabeth; Nguyen, Kayla; Pantoja, Monzerrat; Chaudhari, Mitali; Sandholm, Phoebe; Yoon, Eric; Harrison, Henry F.; Boutros, Sydney; Hirsch, Alec J.; Raber, Jacob (Frontiers in Immunology, 2024)
IntroductionThe effects of viral infections might be apolipoprotein E (apoE) isoform-dependent. In humans, there are three major apoE isoforms, E2, E3, and E4. E4 is associated with the enhanced entry of several viruses into the brain and their disease progression. A concern of infection by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is the development of post-acute COVID-19 syndrome, also known as long COVID. Genetic risk factors for developing long COVID were reported.MethodsIn this study, we used virus-like particles (VLPs) that include expression of the SARS-CoV-2 nucleocapsid (N), membrane (M), and envelope (E) structural proteins together with S. In the current study, we used human E2, E3, and E4 targeted replacement mice to assess whether these VLPs affect body weight, behavioral and cognitive performance, and circadian body temperatures. Using VLPs allow working outside an ABSL-3 facility.ResultsThe effects of VLPs on some behavioral measures were apoE isoform-dependent, with the E2 mice being more affected than E3 or E4 mice. The overall decreased activity in the open field containing objects in week 2 indicate that VLPs can also reduce activity levels in an apoE isoform-independent fashion.DiscussionThe results of the current study indicate that even in the absence of viral replication, detrimental effects of VLPs on behavioral measures and circadian body temperatures are seen.